The association between family functioning and problem behaviors among Chinese preschool left-behind children: the chain mediating effect of emotion regulation and psychological resilience - Qiao, Tianqi; Sun, Yan; Ye, Pingzhi; Yan, Jingfeng; Wang, Xinxin; Song, Zhanmei (Frontiers in Psychology, 2024)
The family environment has a significant impact on the psychological and behavioral development of children, especially those who are left behind in preschool and experience parent-child separation at a young age. These children face a greater risk of family dysfunction, which can lead to internalizing and externalizing problem behaviors. While numerous studies have established a connection between family functioning and problem behaviors, few have explored the underlying mechanisms driving this relationship. Our study seeks to address this gap by examining how emotion regulation and psychological resilience mediate the link between family functioning and problem behavior. The sample consisted of 940 preschool children (51.5% male, 48.5% female) with a mean age of 5.07±0.80. The main guardians of the children were given the Family Assessment Device, Preschool Children's Emotion Regulation Scale, the Devereux Early Childhood Assessment for Preschoolers (2nd edition), and the Social Skills Improvement System-Rating Scales to assess their family functioning, emotion regulation, psychological resilience, and problem behavior respectively. The research conclusions are as follows: firstly, lower family functioning was associated with more severe problem behaviors in preschool left-behind children, and emotion regulation and psychological resilience partially mediated the relationship between family functioning and problem behaviors, respectively; in addition, emotion regulation and psychological resilience were also chain mediators between family functioning and problem behaviors; finally, the study's findings highlighted the crucial role of emotional regulation and psychological resilience in the correlation between family functioning and problem behaviors. It is recommended that policymakers and educators place a high priority on the cultivation of internal psychological resources, such as emotional regulation and resilience, in preschool-aged children when designing interventions to address problem behaviors.